LITERACY AND CREATIVITY OF PRIMARY SCHOOL CHILDREN THROUGH THE IMPLEMENTATION OF STUDY GUIDANCE - Nada Dwi Fadillah; Rika Zuliani, Azyla Febri (International Journal of Students Education, 2023)
Community service activities (PKM) are carried out by students of Muhammadiyah University of North Sumatra. PKM participants totaled eight female students who were guided by a field supervisor (DPL) appointed by Muhammadiyah University of North Sumatra. This PKM was carried out within a month with 3 programs from 24 August to 22 September 2023. Humans as living beings must experience development at every time, including children of primary age (7-13 years). One important aspect of development is the cognitive aspect. This research addresses the problem of low literacy and creativity among today’s children by implementing a "Tutoring" program. Through observation, analysis and coordination with non-formal methods, as well as activities such as private tutoring, the program has successfully increased students’ interest in reading, their creativity and literacy skills. This study aims to determine whether there is a relationship between parental guidance on literacy and creativity in the application of student learning. The estimated results of simple observation and analysis show that the variable of people’s tutoring affects students’ learning creativity with a Sig value. 0.000 <0.05 with a coefficient of determination of 0.582 or 58.2%. This means that the parental tutoring variable contributes 58.2% to the learning creativity of students or children, the remaining 41.80% comes from other factors that are not observed. So as researchers we provide cognitive development among their activities to overcome the problem of low literacy and creativity in children. So it can be concluded from this factor that is less observed.